Kuasa Simbolik Tokoh Blater Dalam Kontestasi Politik Lokal Di Madura: Studi Kasus Strategi Komunikasi Politik Pilkada Bangkalan 2024 - Jadid, Moh Nurul; Jupriono; Dey Prayogo (Public Sphere Review, 2025)
This research analyzes the symbolic power of blater figures in political communication strategies during the 2024 Bangkalan Regional Head Election, particularly examining how informal actors mobilize electoral support despite minimal institutional backing. This qualitative case study employed in-depth interviews with four key informants (blater figures, village heads, political observers, and community members) alongside participatory observation of informal social spaces. Data were analyzed using Miles and Huberman's interactive model with triangulation for validity. Blater's symbolic power is constructed through the accumulation of social capital (extensive cross-class networks), cultural capital (mastery of ajhâgâ and tengka values), and economic capital (selfless generosity), which are converted into symbolic capital. Their political communication operates implicitly through informal spaces (sandur, to'otok) with simple messages like "tang oreng" that are effective due to long-term moral legitimacy. Candidate pair number 2, supported by only three non-parliamentary parties, obtained 39.8% of votes, approaching the 60.2% of pair number 1 supported by 12 major parties. limitations/implications: This study is limited to Bangkalan District, which may affect generalizability. Future research could examine comparative dynamics in other Madurese or Indonesian regions with similar honor cultures. Political parties should engage informal community leaders to enhance trust and voter mobilization. Campaign strategies should integrate local values rather than relying solely on formal institutional structures. This research contributes to Bourdieu's symbolic power theory by demonstrating its application in non-Western honor cultures, revealing that moral legitimacy can be more efficient than formal party structures in electoral mobilization.